Design of a Sampling System for chemical, radiological, and biological reconnaissance vehicles - Lê Đức, Anh; Nguyễn Văn Ngân (Journal of Military Science and Technology, 2024)
This paper presents a computational solution for the design of a sampling system for a Chemical, Biological, Radiological, and Nuclear (CBRN) reconnaissance vehicle. The system is capable of collecting soil, dust, and water samples on various terrains. The sampling system consists of a robotic arm with three degrees of freedom that is controlled from inside the vehicle. The use of the sampling system allows soldiers to collect samples in harsh environmental conditions for analysis or to be sent back to laboratories. The system is designed to ensure high accuracy, reliability, and safety.